331 Association Between Radiation Necrosis and Tumor Biology Following Stereotactic Radiosurgery for Brain Metastasis. (1st August 2016) - Miller, Jacob A.; Bennett, Elizabeth Emily; Xiao, Roy; Kotecha, Rupesh; Chao, Samuel T.; Vogelbaum, Michael A.; Barnett, Gene H.; Angelov, Lilyana; Murphy, Erin; Yu, Jennifer; Ahluwalia, Manmeet; Suh, John H.; et al.
Abstract: INTRODUCTION: Over the past decade, there has been tremendous interest in biological risk stratification and precision medicine. The chief dose-limiting toxicity of stereotactic radiosurgery (SRS) is radiation necrosis (RN), which occurs following approximately 5% to 10% of treatments. This complication may worsen neurological deficits, increase the frequency and cost of imaging, and necessitate prolonged treatment with steroids or antiangiogenic agents. We hypothesized that tumor biology is associated with RN, and that biological risk stratification may be used to guide dose escalation and dose reduction. METHODS: All patients presenting with brain metastasis between 1997 and 2015 who underwent SRS at a single tertiary-care institution were eligible for inclusion. The primary outcome was the cumulative incidence of radiation necrosis, which was diagnosed based on pathological and/or radiographic evidence with the expertise of a tumor board. Multivariate competing risks regression was used to identify independent predictors of RN. RESULTS: Among 1939 included patients (5747 lesions), 285 (15%) developed RN following treatment of 427 (7%) lesions. After SRS, the 6-, 12-, and 18-month cumulative incidences of RN were 3.2%, 5.6%, and 6.7%. Following multivariate analysis, prognostic group, renal pathology, left-sided lesions, lesion diameter, and the homogeneity index remained independently predictive of RN. In subset analyses, HER2-amplified status (hazard ratio [HR], 2.05, P = .02), BRAF V600E+ mutational status (HR, 0.33; P = .04), adenocarcinoma histology (HR, 1.89; P = .04), and ALK rearrangement (HR, 6.36; P < .01) were associated with RN. The rate of RN was nonsignificantly increased among EGFR+ lesions (HR, 1.65; P = .20). CONCLUSION: Strategic dose adjustment may offer superior local control while sparing the morbidity and cost associated with RN. In the present investigation, we report the largest series of lesions developing radiation necrosis, and identify biological features associated with this complication, including adenocarcinoma histology, HER2 amplification, and mutations of the BRAF and ALK genes. Future studies determining the optimal timing of targeted therapies and SRS are warranted.